Adherence to exercise interventions in older people with mild cognitive impairment and dementia: A systematic review and meta-analysis - Di Lorito, Claudio (Prev Med Rep, 2020)
Adherence to physical exercise is associated with multiple benefits in people with mild cognitive impairment (MCI) and dementia. Given the gap in research, this systematic literature review aimed to determine in the context of exercise intervention studies for people with MCI and dementia: 1. How adherence is defined, monitored and recorded; 2. Adherence rates; 3. Attrition, compliance and adverse events and 4. Intervention characteristics associated with adherence. Embase, Medline, PsychInfo, SPORTDiscus, AMED, CINAHL and the International Bibliography of Social Sciences were searched in November 2018. The data were analyzed through descriptive and correlation/inferential statistics. Forty-one studies were included, 34 involving participants with dementia (n = 2149) and seven participants with MCI (n = 970). Half of the studies operationally defined adherence. Mean adherence rate was 70% [CI, 69–73%]. Adherence was significantly associated with endurance/resistance training, and interventions not including walking. The review found a lack of consistency around reporting of adherence and of key variables mediating adherence, including compliance, attrition and adverse events. Further research using more reliable measures is needed to confirm whether a correlation exists between length of interventions and adherence in participants with MCI and dementia and to identify the factors or strategies that mediate adherence in this population. Relevant implications for practice include a consideration in the development of new interventions of elements associated with higher adherence in this review, such as endurance/resistance training, and the provision of exercise in group formats.